Dosimetric comparison of 3D-Conformal and IMRT techniques used in radiotherapy of gastric cancer: A retrospective study - gul, osman vefa; Demir, hikmettin; Kanyilmaz, Gul; Cakır, Tahir (International Journal of Computational and Experimental Science and Engineering, 2024)
This study aimed to compare three-dimensional conformal radiotherapy (3D-CRT) and intensity-modulated radiotherapy (IMRT) planning techniques commonly used in gastric cancer radiotherapy with dose volume histograms. Computed tomography (CT) images of 20 gastric cancer patients were retrospectively analyzed. 3D-CRT, 5F- IMRT and 7F- IMRT treatment plans were created for each patient. The 3 plans were compared on dose volume histogram (DVH). 3D-CRT, 5F-IMRT and 7F-IMRT plans achieved a prescribed dose of 45 Gy for 95% of PTV volume. D95 values were 45.06±0.47 Gy for 3DCRT, 46.39±0.38 Gy for 5F-IMRT and 45.20±0.11 Gy for 7F-IMRT. In 3D-CRT, 5F-IMRT and 7F-IMRT techniques, the 13 Gy receiving volumes of the right kidney were found to be 35.08+9.59, 36.25+7.97 and 37.03+9.03 respectively. Moreover, the volume of the right kidney receiving a 20 Gy and 30 Gy dose received less dose with 5F-IMRT than with 7F-IMRT. Since each patient’s critical organs are at different distances from the target and each technique has its own advantages in terms of critical organs, we suggest that the useful technique should be decided by clinical consensus.